Genome-wide identification of the JAZ gene family in non-heading Chinese cabbage and the functional verification of BcJAZ2 in the biosynthesis of β-caryophyllene - Tiantian Han; Haibin Wang; Zhile Liang; Aimei Bai; Huanhuan Xu; Jianjun Wang; Tongkun Liu; Xilin Hou; Ying Li (Vegetable Research)
JASMONATE ZIM DOMAIN (JAZ) proteins function as negative regulators of the JA signaling pathway and participate in plant development, stress responses, and secondary metabolism. β-caryophyllene is a volatile sesquiterpene compound that contributes to the formation of plant aromas and possesses antibacterial, anti-inflammatory, and antifungal biological activities. In our previous experiments, we found that the BcJAZ2 was closely related to β-caryophyllene synthesis under low-temperature treatment in non-heading Chinese cabbage (NHCC). To further explore the function of BcJAZ2, we characterized JAZ gene family in NHCC. In this study, 25 BcJAZ genes were discovered in NHCC, and comprehensively analyzed the evolutionary relationships and structural characterizations of BcJAZs. BcMYC2, a positive regulator of terpenoid synthesis, interacted with BcJAZ2 confirmed by yeast two-hybrid and bimolecular fluorescence complementation assays. Overexpression of BcJAZ2 in Arabidopsis and silencing of BcJAZ2 in NHCC showed that BcJAZ2 acted as a negative regulator of β-caryophyllene biosynthesis. In addition, three transcription factors BcbHLH137, BcHBI1.1, and BcHBI1.2 were confirmed to be positive regulators of BcJAZ2 by yeast one-hybrid and LUC assays. The above results enrich our understanding of the regulation of β-caryophyllene synthesis and provide the foundation for in-depth exploration of regulatory mechanisms of BcJAZs.